50 Years of international journal of systems science: a review of the past and trends for the future. Issue 8 (11th June 2021) - Wang, Xinxin; Chang, Yurui; Xu, Zeshui; Wang, Zidong; Kadirkamanathan, Visakan
Abstract : International Journal of Systems Science ( IJSS ) is an international journal in the fields of Automation & Control Systems, Computer Science, and Operations Research & Management Science. This paper is a celebration of the 50th anniversary of IJSS . A Web of Science count of 7528 documents were derived from 1970 to 2019 as data sources for the bibliometric analysis. First, the fundamental characteristics of the documents were identified from the bibliometric indicators, and features of keywords were revealed over the half century. A timeline and occurrence analyses were conducted via the software tools, through which popular keywords were visualised in different time periods. These were then grouped into four categories by a hierarchical clustering method, and emerging keywords were selected using burst detection analysis. This was followed by the Autoregressive Integrated Moving Average modelling to predict the future research trends in the four clusters as evidenced in the historical data. Documents were discussed in the recent 20 years towards guiding scholars in three aspects, i.e. problems addressed, popular methodologies, and impact in the relevant fields. Finally, a summary of the main findings was given in the conclusions.